2016
DOI: 10.1021/acs.energyfuels.6b01370
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Aviation Turbine Kerosene Nanofluid Fuel Containing Boron Nanoparticles

Abstract: The present work studies the thermal and physical properties of aviation turbine kerosene (ATK)–boron nanofuels, including stability time, viscosity, thermal behavior, and energy content. Also, this study tries to explore the effects of the size and concentration of boron particles, surfactant type, and temperature on the stability and viscosity of nanofuel. Nanofuel samples were prepared and characterized at 0.5–4 wt % of particle loading and 0.1–2 wt % of surfactant loading ranges, for micro- and nanosized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…178 Shariatmadar et al reported the synthesis and characterization of aviation turbine kerosene nanouid fuels and nano-fuels containing BNPs. 72,73 These results powerfully verify great prospects of 0D boron nanomaterials and derivatives that serve as promising energetic materials for applications in the additive nanouid fuels and nano-fuels.…”
Section: Ignition and Combustionmentioning
confidence: 68%
See 4 more Smart Citations
“…178 Shariatmadar et al reported the synthesis and characterization of aviation turbine kerosene nanouid fuels and nano-fuels containing BNPs. 72,73 These results powerfully verify great prospects of 0D boron nanomaterials and derivatives that serve as promising energetic materials for applications in the additive nanouid fuels and nano-fuels.…”
Section: Ignition and Combustionmentioning
confidence: 68%
“…With regard to the top-down synthesis approach, mechanical milling is extensively employed to prepare 0D boron nanomaterials. 68,69,[71][72][73][74][75][77][78][79][80]82,85,89 Mechanical milling is divided into different types, including dry ball milling, neat ionic-liquid (IL) milling, solvent milling, sonication-assisted milling, articial and machine grinding. The operation of mechanical milling is oen continuously conducted for a few, several and even dozens of hours at low temperature or room temperature (RT).…”
Section: Mechanical Millingmentioning
confidence: 99%
See 3 more Smart Citations